ABORDĂRI TEORETICE ÎN CONTEXTUL PEDAGOGIC AL TRIADEI RELAŢIONALE - OBIECTIVE /COMPETENŢE/ PERFORMANŢE ÎN PROCESUL DE ÎNVĂŢARE - USM ADMIN (Moldova State University, 2009)
Nowadays it is becoming increasingly imperative to develop an updated approach to human education that would allow for the development of capacities and competencies in students in a comprehensive manner, leading in turn to performances. At the beginning of the new millennium, education is conditioned by behaviors and skills necessary for personal and professional achievements and ought to become anticipative, progress-oriented, creative and centered on personality development. The traditional education system, focused preponderantly on informative substance to the disadvantage of the development content, is outdated and needs to be replaced by an adequate education system focused on conditioning behavior changes. A holistic framework is needed, correlating formative education with assimilating information. The strategy of contemporary learning is to reach a balance between the two components, still leaning on the formative essence. A proper set-up for the education and learning process, in line with current developments, needs to begin with clearly-established goal, objectives, and process and defining key theoretical concepts.